Ringing does not appear to have an adverse effect on body mass immediately following capture in Eurasian Teal Anas crecca - Guillemain, Matthieu; Cavallo, Francois; Massez, Gregoire; George, Thierry; Baudet, Jean-Pierre; Gonzalez, Pierre; Ducasse, Valerie; Caillot, Emmanuel; Lecaplain, Benoit; Tison, Luc; Piffeteau, Natacha; Aretel, Jean-Pierre; et al. (Wildfowl, 2015)
Studies of waterbirds rely to a large extent on ringing and resighting or recapture data, whilst assuming that ringed birds are broadly representative of the population as a whole. This may not be the case if the capture process may in itself have an influence on the birds. The analyses presented here showed that the body mass of ringed ducks often decreases between capture and recapture if the latter occurs within a few days or weeks. This could possibly reflect stress caused by handling, which would be problematic if it causes ringed birds to behave in a way that differs from the population as a whole. Alternatively, body mass measurements could also be biased by the general use of bait to attract birds to the trap. Initial and subsequent body mass data recorded for Eurasian Teal Anas crecca caught then recaptured within three weeks were compared between sites where the birds were attracted to traps with bait or with live decoys. When bait was used individuals had a greater body mass at ringing but were lighter at recapture at all but one site, where only a marginal difference was found. Conversely, when using live decoys, body mass remained constant at the next capture event. This suggests that mass loss commonly observed between capture and recapture is not caused by handling, but is potentially an artefact linked to duck hyperphagia in the presence of abundant food at ringing. It also implies that most available duck body mass data, which are usually obtained from birds ringed at baited traps, may be artificially inflated. The present results are based on one single unbaited site, however, and experimental manipulative studies (alternating the use of bait and live decoys to trap birds) are needed to confirm the findings.